The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1080/15287399309531760
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of muscarinic receptors and the m3 subtype in white‐footed mice by dietary exposure to parathion

Abstract: The effect of ad libitum dietary exposure (as occurs in the field) to parathion for 14 d was investigated on the muscarinic acetylcholine receptor (mAChR) in brains and submaxillary glands of adults of a field species, the white-footed mouse Peromyscus leucopus. Immunoprecipitation using subtype selective antibodies revealed that the relative ratios of the m1-m5 mAChR subtypes in Peromyscus brain were similar to those in rat brain. There was little variability in acetylcholinesterase (AChE) activity in control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…Organisms have several potential adaptations to ChE inhibition, including increased synthesis of ChE (Abbas and Hayton, 1997), decreased synthesis of ACh (Liu and Pope, 1996), and desensitization and downregulation of MChR (Jett et al, 1993;Nostrandt et al, 1997). Regression of B and K " against ChE activity is a measure of the response of MChR to ChE inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Organisms have several potential adaptations to ChE inhibition, including increased synthesis of ChE (Abbas and Hayton, 1997), decreased synthesis of ACh (Liu and Pope, 1996), and desensitization and downregulation of MChR (Jett et al, 1993;Nostrandt et al, 1997). Regression of B and K " against ChE activity is a measure of the response of MChR to ChE inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Again, the degree of reduction in muscarinic agonist binding was greater in adult than in aged tissues. Numerous studies have demonstrated that prolonged acetylcholinesterase inhibition leads to adaptive down-regulation of muscarinic receptors (Costa et al, 1982;Russell and Overstreet, 1987;Jett et al, 1993;Pope et al, 1995). PS exposure has been shown to affect different subpopulations of muscarinic receptors in the adult rat brain (Chaudhuri et al, 1993;Olivier et al, 2001b).…”
Section: Discussionmentioning
confidence: 95%
“…This spread is greater than the 2.4-fold difference reported here in control animals (Table 2). In another example, Jett et al (1993) reported that a normal range of AChE activity existed between 70 and 100 (arbitrary units) in the brains of control white-footed mice. By establishing such a range, they showed that following parathion exposure enzyme activity ranged between 25 and 95 in animals exposed to 100 ppm parathion and was less than 30 in the 500 ppm group.…”
Section: Discussionmentioning
confidence: 96%